Avaliação do efeito anticonvulsivante do geraniol e do complexo de inclusão geraniol:β-ciclodextrina em camundongos - Lins, Lívia Cristina Rodrigues Ferreira (2013)
Geraniol (GR) is an acyclic monoterpene alcohol component of essential oils of several aromatic plants used by Brazilian folk medicine for the treatment of epilepsy. However, there are no studies in literature that report effects of GR on Central Nervous System, specifically its potential anticonvulsant effect. The aim of this study was to investigate the anticonvulsant effect of GR and of inclusion complex GR: β-cyclodextrin (GR: β-CD) in animal models of epilepsy induced by Pentilenotetrazole (PTZ) or Strychnine (STR). Initially, mice Swiss male were pretreated, acutely, with GR or GR: β-CD at doses of 50, 100 or 200mg/kg, i. p., 30 minutes before of PTZ administration. The latency of first convulsion and the frequency of convulsion and death were observed for a period of 15 minutes after the administration of convulsant stimuli. The results showed that pre-treatment with GR at dose of 200mg/kg and with GR: β-CD at doses of 100 and 200mg/kg significantly increased the latency of first convulsion and reduced the frequency of animals that convulsed. The procedures were repeated in STR-induced convulsion model, however only the effects of pretreatment with GR were evaluated and no significant effect of GR were observed in this model. The results indicate that GR has an anticonvulsant effect, possibly mediated by GABAergic mechanisms, and the encapsulation of GR in β-CD improved this effect, probably by increase of bioavailability of GR.